(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
Scientific thinking depends on the accomplishment of several stages, considered classic for the accomplishment of a scientific investigation. Among them, the theoretical framework that supports the search for a response to a problem question. The purpose of this article is to better understand the construction of scientific researches within a highly qualified Brazilian masters program, by verifying the types of sources that constitute the theoretical references of its thesis. It was identified that most of the references were based on books, which raised doubts as to whether the authors of these thesis were actually willing to benefit from more contemporary or innovative research, a classic feature of articles published in journals.